Better Living through Chemistry: Caloric Restriction (CR) and CR Mimetics Alter Genome Function to Promote Increased Health and Lifespan - Gillespie, Zoe E.; Pickering, Joshua; Eskiw, Christopher H. (Frontiers in Genetics, 2016)
Caloric restriction (CR), defined as decreased nutrient intake without causing malnutrition, has been documented to increase both health and lifespan across numerous organisms, including humans. Many drugs and other compounds naturally occurring in our diet (nutraceuticals) have been postulated to act as mimetics of caloric restriction, leading to a wave of research investigating the efficacy of these compounds in preventing age-related diseases and promoting healthier, longer lifespans. Although well studied at the biochemical level, there are still many unanswered questions about how CR and CR mimetics impact genome function and structure. Here we discuss the impact of CR and potential CR mimetics on genome function and structure, including changes in gene expression profiles and epigenetic modifications and their potential to identify the genetic fountain of youth.